Pengembangan kendaraan listrik autonomous berdasarkan pandangan futuristik Michio Kaku - Fred Soritua Manurung; Agus Sachari (PRODUCTUM Jurnal Desain Produk (Pengetahuan dan Perancangan Produk), 2020)
Autonomous electric vehicle development became a new trend nowadays, dealing with reducing supply possibility of the mineral fuel and the purposes of pressing the waste gas from the combustion vehicle engine. Electric Autonomous vehicle thrived according to the development of information and telecommunication technology, semiconductor technology, chemistry technology which allows building long-range sending and receiving communication system with very high speed and massive data also long time duration for battery usage as well as the efficiency of electric motor escalating.Autonomous electric vehicle has become the focus for the vehicle development in 2020 and many countries start to running test the system. Prediction according to this subject has been reveal by Michio Kaku as a physicist and famous futurist. As a physicist who developed the science and invention of the new technologies for future usage, it was unchallenged Michio Kaku could be confided around this subject, such as the internet technology and information also technology related to human health including the nanotechnology became tiny and reachable, according to Michio Kaku. Technology could be used as a product, the prediction will be beneficial if connected to Indonesian vehicle development especially if associated with the rural area as a unique condition, which distinguishes consecrating to city area in the other countries.Keyword : autonomous, electric vehicle, futurist view, Michio Kaku